Exploring Human Limitations in Robert Frost's Poetry: Themes of Boundaries, Isolation, and Societal Constructs. (IUBAT Review, 2025)
This paper explores the thematic representation of human limitations in the poetry of Robert Frost, a seminal figure in 20th-century literature. Frost’s work investigates the multifaceted dimensions of human limitations—socio-economic, emotional, intellectual, and existential—reflecting the struggles individuals face within societal expectations, natural indifference, and their own internal confines. Through vivid imagery and layered narratives, Frost examines the tension between human aspirations and the limitations  imposed by external and internal forces, subtly critiquing broader systems and ideologies that shape these experiences. By applying critical frameworks, including Marxist literary theory, this study reveals Frost’s nuanced engagement with the universal human condition, emphasizing the persistence of individuals to navigate and transcend their limitations in pursuit of meaning and self-realization. This analysis offers a comprehensive understanding of Frost’s portrayal of human resilience amidst the inexorable challenges of existence.IUBAT Review—A Multidisciplinary Academic Journal, 8(1): 243-257